Using linked open data to improve the search of open educational resources for engineering students - Piedra Pullaguari, N. (2013)
In this paper, authors apply the Linked Data Design Issues to describe and retrieve information that is semantically related to open educational resources related to the Engineering Education, that are accessible via the OCW Higher Institutions. Linked data have the potential of create bridges between OCW data silos. To assess the impact of Linked Data in OCW, the authors present an interface of faceted search for open educational content. The authors demonstrate that OCW resource metadata related to engineering open courses can be consumed and enriched using datasets hosted by the LinkedOpenData cloud.